Knowledge of Ardabil dentists regarding dental treatments in patients undergone chemotherapy procedures - Hajmohammadi, Emran; Bagheri, Abolfazl; Yazdani, Javad; Nezafati, Saeed; Mohammadzadeh, Asghar (International Journal of Advances in Medicine, 2017)
Background: Oral cancer is less than 3% of all malignant tumours in the body and is the sixth most common cancer in men and the twelfth most common cancer in women. Now, for the treatment of cancer patients of different treatment methods are used which one of them was chemotherapy and dentists should be considered a person with cancer and is undergoing chemotherapy and skills needed to be aware of. Methods: This cross-sectional study has been done on 124 general dentists in Ardabil province. Data collected by a questionnaire and analysed by statistical methods in SPSS 19. The knowledge rate divided in three groups; week, moderate and good. Results: 50 women and 74 men with a mean age of 35 years. The knowledge rate of dentists in age < 35 was higher than dentists with age >45 years. The knowledge rate was in moderate level and in women was differently from men. Dentists under 10 years work experience have knowledge rate upper than dentists over 10 years of work experience. Conclusions: The results showed that knowledge level of dentists in Ardabil in conjunction with chemotherapy patients was in moderate level. So, for raising the knowledge rate of dentists we need to program training courses in continuous education.